2002
DOI: 10.1007/s10071-002-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Bee-eaters ( Merops orientalis ) respond to what a predator can see

Abstract: Two sets of experiments are reported that show that the small green bee-eater ( Merops orientalis, a small tropical bird) can appreciate what a predator can or cannot see. Bee-eaters avoid entering the nest in the presence of a potential nest predator. In the first set of experiments bee-eaters entered the nest more frequently when the predator was unable to see the nest from its position, as compared to an approximately equidistant position from which the nest could be seen. In the second set of experiments b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…The presence and size of the beak of a female may be a useful visual feature to evaluate mates in terms of the efficacy of feeding and parasite control. The finding that the manipulation of the eyes did not have as strong an effect as the beak appears to be counterintuitive because previous studies showed that avian eye models triggered robust reactions [Blest, 1957;Scaife, 1976;Emery, 2000;Watve et al, 2002]. The main difference between these studies and the study by Patton et al [2010] is whether stimulus eyes belong to dangerous predators or harmless conspecifics.…”
Section: Significance Of the Facementioning
confidence: 79%
“…The presence and size of the beak of a female may be a useful visual feature to evaluate mates in terms of the efficacy of feeding and parasite control. The finding that the manipulation of the eyes did not have as strong an effect as the beak appears to be counterintuitive because previous studies showed that avian eye models triggered robust reactions [Blest, 1957;Scaife, 1976;Emery, 2000;Watve et al, 2002]. The main difference between these studies and the study by Patton et al [2010] is whether stimulus eyes belong to dangerous predators or harmless conspecifics.…”
Section: Significance Of the Facementioning
confidence: 79%
“…At first sight, we might suppose that the responses to the orientation of the predator, to whether the eyes are covered and to the direction of the predator's eye-gaze suggest that starlings are able to recognize when a predator is looking at them and infer the likelihood that they will consequently be chased. Indeed, the idea that 'from a gaze cue the animal understands where and what a human can see' is the sort of interpretation that has been offered in some studies of animal responses to human gaze cues (including Smitha et al 1999;Watve et al 2002;Kaminski et al 2004;Bräuer et al 2005). While we do not deny the interesting possibility that starlings might have a cognitive appreciation of the knowledge state of their predator through recognizing the predator's visual perspective, this type of explanation may not be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Hampton 1994;Watwe et al 2002) that birds may be sensitive to the visual behaviour of humans. In response to human look-cues, ravens changed their orientation immediately and in the predicted direction.…”
Section: Discussionmentioning
confidence: 99%